UJI EFEKTIVITAS INSEKTISIDA TERHADAP HAMA Maruca testulalis PADA BIBIT MALAPARI (Pongamia pinnata (L.) Pierre) - Benyamin Dendang; Endah Suhaendah (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
Maruca testulalis is one of pest on leaves of Pongamia pinnata (L.) Pierre. leaf in nursery. The objective of this research was to compare the efficacy of insecticides on larvae population and degrees of damage intensity. The research used complete randomized design with five treatments and three replications. The treatments were control, azadirachtin 5 g/l, Bacillus thuringiensis 1 g/l, klorantraniliprol 1 g/l and monosultap 0.5 ml/l. The results showed that tested insecticides influence on the intensity of M. testulalis. Klorantraniliprol azadirachtin and monosultap insecticides were more effective to control the larvae of M. testulalis when compared to B. thuringiensis.